1970
DOI: 10.5713/ajas.2013.13248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single Nucleotide Polymorphisms (SNPs) of the Bovine Growth Hormone (bGH) Gene Associated with Growth and Carcass Traits in Hanwoo

Abstract: The purpose of this study was to find any association of the bovine growth hormone (bGH) gene with growth and carcass quality traits in Korean native cattle, Hanwoo. Genomic DNA was extracted from 21 Hanwoo individuals, and the 47 to 2,528 bp region of the bGH 2,856 bp (GenBank accession number M57764) including the promoter and the five exons was sequenced. A total of ten bGH SNPs were confirmed, including four (253 C>T, 303 C>T, 502 C>T, and 559 G>A) in the promoter, one (679 C>T) in exon 1, one (1,692 T>C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Dybus (2002) also confirmed that SNP g.1047C>T was associated with milk quality in Polish Black-and-White cattle. In addition, Lee et al (2013) reported that the SNP g.1642C>G was associated with daily weight gain in the Hanwoo (Bos taurus) cattle with moderate PIC value. In contrast, Agung et al (2017) reported that SNP g.1047C>T was not associated with birth weight, weaning weight, yearling weight, and dressing percentage in the SO cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Dybus (2002) also confirmed that SNP g.1047C>T was associated with milk quality in Polish Black-and-White cattle. In addition, Lee et al (2013) reported that the SNP g.1642C>G was associated with daily weight gain in the Hanwoo (Bos taurus) cattle with moderate PIC value. In contrast, Agung et al (2017) reported that SNP g.1047C>T was not associated with birth weight, weaning weight, yearling weight, and dressing percentage in the SO cattle.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was mentioned by another group in Indonesia [18] who reported the same C>T SNP as a new mutation in The second mutation (2258 bp C>T) appeared in the two strains of Baggara cattle. The 2258 C>T SNP was previously associated with average daily weight gain (ADG) and carcass weight (CWT) [19] . The high allele frequency of the favorable allele (C) in both European and Asian Bos taurus breeds indicated that selection for genetic improvement of ADG and CWT is associated with the SNP or a locus at Linkage disequilibrium with the SNP [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The 2258 C>T SNP was previously associated with average daily weight gain (ADG) and carcass weight (CWT) [19] . The high allele frequency of the favorable allele (C) in both European and Asian Bos taurus breeds indicated that selection for genetic improvement of ADG and CWT is associated with the SNP or a locus at Linkage disequilibrium with the SNP [19] . There is a need to further investigate this important mutation in all strains of Baggara cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The AluI polymorphism is associated with the replacement of bases C-G in the 5th exon of the bGH gene, as a result the amino acid Leu is replaced with the amino acid Val (L127V, rs 4192384). There is an association of various polymorphic variants of the bGH gene with different productive traits in cattle [13].…”
Section: Introductionmentioning
confidence: 99%